Метод прогнозирования продаж и оценки спроса товаров при помощи аппарата временных рядов - Грабовская, Е. С. (ХНУРЕ, 2019)
This work is dedicated to creating a customer relationship management application and based on application‘s data build a time series forecast to predict sales and demand for certain products. This CRM application will help to maintain contact with clients, log calls, keep a record of deals and have access to customer‘s data, that is shared by customer, to offer better options for each client. To help the manufacturer to exclude irrelevant products and have an insight into forecasted sales based on existing data of sales, the application will also provide a time series long-term and short-term forecasts.